analysis of biomass on fauna of a system of water catchment in a thermal power plant through environmental monitoring - Gouveia, Renata Laranjeiras; Rodrigues, Midiã da Silva; Melo, Karina Galvão de; Fernandes, Múcio Luiz Banja; Silva, Andréa Karla Pereira da (Revista Nordestina de Zoologia, 2012)
The environmental tracking is an effective technique to get the level of negative impact that occasionally may happen in a determined area. Because of its fast results and ecologically prudent techniques, in which there isn’t a loss of the fauna variety, the environmental tracking has become a way for researchers to reach an environmental sustainability and to assure that the natural environment and aquatic biodiversity do not suffer any huge impact. The research was developed in the Thermoelectrical Plant of Pernambuco (TERMOPE), located in Suape, and was made up by monthly collection of biological material held back on the suction pumps of marine water and on the discard boxes of the UTE-TERMOPE during the entire year of 2011, which allowed us to do an area tracking of the local biodiversity. After all the material selection, and the separation of the species that were found, and the sample’s total biomass, it was possible to verify that these fauna samples that were collected do not represent any impact to the local used on this study as well as any loss of the environmental biodiversity.